Imperial and Anti-imperial and Translation in Native American Literature (translation. a transdisciplinary journal, 2022)
In this paper I crace a brief history of translation of Native American texts, looking at both imperial and anti-imperial practices and strategies. The opening section discusses a series of omissions and false substitutions by imperialistic translators, whose goals may have been directed more at conversion and domestication than translation proper. I then focus on ethnographic and ethnopoetic translation strategies practiced by anthropologists and literary translators that were less imperial and more open to inclusion and diversity. Finally, I turn to Arnold Krupat's conception of "anti-imperial translation" chat allows Native American terms, sounds, and structures to co-exist in the English language, thereby enlarging the both English and Native American cultures and pointing to a new way of thinking about translation in a (post) translation fashion.